A Petri net approach for performance modelling of polymer electrolyte membrane fuel cell systems - Fecarotti, Claudia; Andrews, John; Chen, Rui (Elsevier, 2016)
Fuel cells are promising technologies for zero-emission energy conversion and power generation. However, durability and reliability are among the main barriers to their commercialisation. Clearly the system performance depends on the reliability of the overall system including both the stack and the balance of plant. This paper seeks to introduce a modelling approach based on the Petri net method for the performance analysis of fuel cell systems. The proposed Petri net model intends to simulate the operation of the fuel cell stack and its supporting system to predict the system performance based on the system structure, along with the components deterioration process. The model considers the causal relationship between the operation of the balance of plant and the fuel cell stack performance. Purging is performed periodically in order to restore some of the voltage loss due to water accumulation or impurities within the cell. Failures of single components of the supporting systems are considered, which will have an immediate effect on the output voltage as well as long term effects on the stack performance.